2011
DOI: 10.4067/s0718-07642011000600014
|View full text |Cite
|
Sign up to set email alerts
|

Fragilización por Hidrógeno de los Aceros API 5L X60 y API 5L X80

Abstract: ResumenSe ha determinado el comportamiento mecánico de los aceros API 5L grados X60 y X80, fragilizados por hidrógeno ambiental y por hidrógeno interno. El potencial y la densidad de corriente para la generación del hidrógeno fueron determinados por polarización potenciodinámica, y el tiempo de saturación estimado a partir de datos de difusividad y solubilidad obtenidos en ensayos de permeación con una célula electroquímica. La carga de hidrógeno para reproducir las condiciones de la fragilización por hidrógen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The results of this work were compared with those obtained in similar studies reported in the literature, in order to validate our results and to determine if similar effects of carbon content and microstructure are observed. The results of Araujo et al [53] were obtained for ferrite-pearlite steels, similar to the P steels tested in this work. The API 5 L-X80 steel with carbon content of 0.084% wt showed a D eff = 3.37 E À06 cm 2 s À1 , while an API 5 L-X60 steel with carbon content of 0.12% wt showed a D eff = 2.11 E À06 cm 2 s À1 , These values are within the same range of the D eff values obtained here.…”
Section: Comparison With Other Worksupporting
confidence: 87%
“…The results of this work were compared with those obtained in similar studies reported in the literature, in order to validate our results and to determine if similar effects of carbon content and microstructure are observed. The results of Araujo et al [53] were obtained for ferrite-pearlite steels, similar to the P steels tested in this work. The API 5 L-X80 steel with carbon content of 0.084% wt showed a D eff = 3.37 E À06 cm 2 s À1 , while an API 5 L-X60 steel with carbon content of 0.12% wt showed a D eff = 2.11 E À06 cm 2 s À1 , These values are within the same range of the D eff values obtained here.…”
Section: Comparison With Other Worksupporting
confidence: 87%